Assessment of CO2 Storage Potential in Naturally Fractured Reservoirs With Dual‐Porosity Models. Issue 3 (8th March 2018) - March, Rafael; Doster, Florian; Geiger, Sebastian
Abstract: Naturally Fractured Reservoirs (NFR's) have received little attention as potential CO2 storage sites. Two main facts deter from storage projects in fractured reservoirs: (1) CO2 tends to be nonwetting in target formations and capillary forces will keep CO2 in the fractures, which typically have low pore volume; and (2) the high conductivity of the fractures may lead to increased spatial spreading of the CO2 plume. Numerical simulations are a powerful tool to understand the physics behind brine‐CO2 flow in NFR's. Dual‐porosity models are typically used to simulate multiphase flow in fractured formations. However, existing dual‐porosity models are based on crude approximations of the matrix‐fracture fluid transfer processes and often fail to capture the dynamics of fluid exchange accurately. Therefore, more accurate transfer functions are needed in order to evaluate the CO2 transfer to the matrix. This work presents an assessment of CO2 storage potential in NFR's using dual‐porosity models. We investigate the impact of a system of fractures on storage in a saline aquifer, by analyzing the time scales of brine drainage by CO2 in the matrix blocks and the maximum CO2 that can be stored in the rock matrix. A new model to estimate drainage time scales is developed and used in a transfer function for dual‐porosity simulations. We then analyze how injection rates should be limited in order to avoid early spill of CO2 (lost control of the plume) on a conceptual anticline model. Numerical simulations on the anticline show that naturally fractured reservoirs may be used to store CO2 . Key Points: We develop an estimate for brine drainage time scales by supercritical CO2 during carbon storage in fractured formations We develop a new transfer function based on this time scale estimate that improves existing transfer functions for dual‐porosity models We illustrate with simulations of injection scenarios into a fractured anticline that carbon storage in a naturally fractured reservoir is possible